MANAGEMENT SYSTEMS IMPLEMENTED TO SUPPORT THE PRODUCTIVITY OF SMALL AND MEDIUM-SIZED COMPANIES - Ramírez Bolívar, Nick Joan
The purpose of the research was to determine the management systems implemented for the productivity of small and medium-sized companies. Methodologically, it is a study with a quantitative, descriptive, non-experimental, field and transactional approach. The population was finite, with a census sample made up of 6 companies from the gastronomic sector of the District of Riohacha; the data collection technique  used was the survey. The analysis was quantitative, supported by a descriptive statistical study. As a result of the investigation, it could be inferred that small and medium-sized companies are not implementing certified management systems to improve their productivity, for reasons of neglect of the existing regulations in this regard, negatively influencing business productivity. It is necessary to implement a strategy that allows the certification of the management systems of these companies, so that they can achieve the expected levels of productivity.